2019
DOI: 10.5194/ms-10-133-2019
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-static axial crushing of hexagonal origami crash boxes as energy absorption devices

Abstract: Thin-walled tubes are widely used as energy absorption devices for their low cost and high manufacturability. Introduction of the origami technique enables the tube to follow a pre-determined failure mode and to improve its energy absorption efficiency. This paper examines the energy absorption characteristics of the origami crash box under quasi-static axial crushing. Both experimental and numerical results show that the origami pattern develops a diamond-shaped mode, bringing a reduction in initial peak forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 31 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…A typical design approach to enhance a vehicle's crashworthiness is to install energy absorption devices that deform and absorb kinetic energy during a low-speed collision (Ma & You, 2014b). Both experimental and numerical results show that the pre-folded pattern develops a diamond-shaped mode, reducing initial peak force and a significant increase in energy absorption compared to the conventional hexagonal tube (Ma et al, 2019). The elevated overall force level, in turn, increases the total energy absorbed.…”
Section: Introductionmentioning
confidence: 95%
“…A typical design approach to enhance a vehicle's crashworthiness is to install energy absorption devices that deform and absorb kinetic energy during a low-speed collision (Ma & You, 2014b). Both experimental and numerical results show that the pre-folded pattern develops a diamond-shaped mode, reducing initial peak force and a significant increase in energy absorption compared to the conventional hexagonal tube (Ma et al, 2019). The elevated overall force level, in turn, increases the total energy absorbed.…”
Section: Introductionmentioning
confidence: 95%
“…The justification for a significant decrease in θ = 110 o was due to the reduction of the designed crosssection area of the Miura origami column. According to [27], the geometry of the column after passing the critical angle θ is expected to withstand more compressive load, but this may not happen since it sacrifices or reduces the designed cross-section area. As a result, it may lower the ability of the column to absorb the strain energy since the column may become slenderer (less stable) and having only a smaller crosssection area that is in contact during the compression testing.…”
Section: Specific Energy Absorptionmentioning
confidence: 99%
“…39 Mesh convergence study was conducted, and a global element size of 2 mm was found suitable and thus adopted in the analysis. In recent publications, 40,41 we presented a similar numerical framework, which has been successfully used and validated in a separate crash box study.…”
Section: Finite Element Modelingmentioning
confidence: 99%